Effective numeracy educational interventions for students from disadvantaged social background: a comparison of two teaching methods. Issue 7 (17th November 2019) - Guilmois, Céline; Popa-Roch, Maria; Clément, Céline; Bissonnette, Steve; Troadec, Bertrand
ABSTRACT: The purpose of this study was to assess the effectiveness of explicit instruction, compared to constructivist instruction, in teaching subtraction in schools with a high concentration of students from a disadvantaged social background: eighty-seven second graders (mean age in months = 90.95, SD  = 5.30). Two groups received explicit versus constructivist instruction during 5 weeks. Pre- and posttest analyses were conducted to compare the effects of the instruction type on subtraction skills taught through the partitioning subtraction method. Results showed that although all students progressed between both evaluations, those who received explicit instruction performed better. The findings from this study suggest that explicit instruction teaching is a promising approach in supporting the learning of mathematical knowledge for low-achieving students from disadvantaged social background. A larger scale study comparing the outcomes of children from different socioeconomic backgrounds would be needed to extend the applicability of the positive effects of this study.